The role of chronotype and reward processing in understanding social hierarchies in adolescence - Judith Lunn; Thomas Wilcockson; Tim Donovan; Frank Dondelinger; Guillermo Perez Algorta; Padraic Monaghan (Brain and Behavior, 2021)
Abstract Introduction Circadian rhythms shift toward an evening preference during adolescence, a developmental period marked by greater focus on the social domain and salience of social hierarchies. The circadian system influences maturation of cognitive architecture responsible for motivation and reward, and observation of responses to reward cues has provided insights into neurocognitive processes that underpin adolescent social development. The objective was to investigate whether circadian phase of entrainment (chronotype) predicted both reward‐related response inhibition and social status, and to explore whether mediator and moderator relationships existed between chronotype, reward processing, and social status outcomes. Methods Participants were 75 adolescents aged 13–14 years old (41 females) who completed an eye tracking paradigm that involved an inhibitory control task (antisaccade task) within a nonsocial reward (Card Guessing Game) and a social reward (Cyberball Game) context. Chronotype was calculated from weekend midsleep and grouped into early, intermediate, and later terciles. Participants indicated subjective social status compared with peers in seven domains. Results An intermediate and later chronotype predicted improved inhibitory control in the social versus nonsocial reward context. Chronotype also predicted higher perceived social status in two domains (powerful, troublemaker). Intermediate chronotypes reported higher “Powerful” status whereas later chronotypes were higher on “Troublemaker.” Improved social reward‐related performance predicted only the higher powerful scores and chronotype moderated this relationship. Improved inhibitory control to social reward predicted higher subjective social status in the intermediate and later chronotype group, an effect that was absent in the early group. Conclusion This behavioral study found evidence that changes toward a later phase of entrainment predicts social facilitation effects on inhibitory control and higher perceived power among peers. It is proposed here that circadian delayed phase in adolescence is linked to approach‐related motivation, and the social facilitation effects could reflect a social cognitive capacity involved in the drive to achieve social rank.